Intraventricular Hemorrhage: Risk Factors and Association With Patent Ductus Arteriosus Treatment in Extremely Preterm Neonates - Khanafer-Larocque, Ijab; Soraisham, Amuchou; Stritzke, Amelie; Al Awad, Essa; Thomas, Sumesh; Murthy, Prashanth; Kamaluddeen, Majeeda; Scott, James N.; Mohammad, Khorshid (Frontiers in Pediatrics, 2019)
Objectives: To assess maternal and neonatal risk factors for intraventricular hemorrhage (IVH). To examine the association of patent ductus arteriosus (PDA) and its treatment, with IVH and its severity. Study design: In this retrospective cohort study, we included preterm neonates born at <29 weeks, admitted to a tertiary level III Neonatal Intensive Care Unit in Calgary, Canada, between 2013 and 2016, who had a head ultrasound in the first 7 days of life. A subset analysis included neonates who also had cardiac ultrasound in the first 3 days of life. Results: Of the 495 neonates, 121 (24.4%) had IVH of any grade and 48 (9.7%) had severe IVH. Identified risk factors were small birth gestation and weight, lack of antenatal corticosteroids, maternal chorioamnionitis, Apgar score <5 at 5 min, umbilical cord pH < 7, respiratory distress syndrome, early onset sepsis, hypercapnia, pCO2 fluctuations, prolonged intubation, inhaled nitric oxide, inotropes or normal saline boluses, metabolic derangements, opioids infusions, and bicarbonate/THAM therapy. In a primary analysis of the total cohort, when the decision to treat a PDA was used as a surrogate marker of its clinical significance, a PDA requiring treatment was associated with a higher risk of IVH. There was no significant difference in the incidence of IVH between neonates with early treatment of a clinically significant PDA compared to late, however early indomethacin treatment was associated with reduced severity of IVH. In the subset analysis, the presence of a hemodynamically significant PDA (hs-PDA) was not associated with a higher probability of IVH. Of those with severe IVH, 18 (55%) had a hs-PDA; this is clinically but not statistically significant. Conclusions: Identified risk factors should be the target of IVH reduction bundles. Early indomethacin treatment for a clinically significant PDA may reduce IVH severity.